Facile preparation of hydrated vanadium pentoxide nanobelts based bulky paper as flexible binder-free cathodes for high-performance lithium ion batteries - Rui, Xianhong (2012)
Hydrated vanadium pentoxide (V2O5•0.44H2O, HVO) nanobelts were synthesized by a simply high-yield